Evaluation of Liver and Spleen Stiffness with Acoustic Radiation Force Impulse Quantification Elastography for Diagnosing Clinically Significant Portal Hypertension - Attia, D.; Schoenemeier, B.; Rodt, T.; Negm, A. A.; Lenzen, H.; Lankisch, T. O.; Manns, M.; Gebel, M.; Potthoff, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: Hepatic vein pressure gradient (HVPG) is the gold standard for diagnosing clinically significant portal hypertension (CSPH). The aim of this study was to investigate—in comparison to HVPG—the ability to diagnose CSPH by liver and spleen stiffness measurements obtained by acoustic radiation force impulse (ARFI) imaging.Materials and Methods: A total of 78 patients (mean age: 53 ± 13 years, 62 % male) with chronic liver disease were enrolled in this study. Each patient received liver (LSM) and spleen (SSM) stiffness measurements by ARFI, an HVPG measurement and a transjugular liver biopsy on the same day. Patients were classified according to their HVPG into three different groups: HVPG < 10 mmHg, HVPG ≥ 10–< 12 mmHg and HVPG ≥ 12 mmHg.Results: LSM, SSM were significantly higher in patients with HVPG ≥ 10 – < 12 in comparison to HVPG < 10 mmHg (p < 0.001 and p < 0.001, respectively), and in patients with HVPG ≥ 12 mmHg in comparison to ≥ 10 – < 12 mmHg (p < 0.001 and p < 0.001, respectively). LSM and SSM were able to diagnose HVPG ≥ 10 mmHg and HVPG ≥ 12 mmHg with high diagnostic performance (AUC LSM: 0.93 and 0.87, respectively; AUC SSM: 0.97 and 0.95, respectively). The AUC of SSM in predicting esophageal varices (EVs) plus HVPG ≥ 10 mmHg and EVs plus HVPG ≥ 12 mmHg were higher compared to LSM in both groups of patients (SSM: 0.90 and 0.93 vs. LSM: 0.84 and 0.88, respectively). No significant difference between both AUCs was detected in the different HVPG groups. In the multivariate analysis SSM remained a factor predicting HVPG (HVPG > 10 mmHg p = 0.007; HVPG ≥ 12 mmHg p = 0.003).Conclusion: LSM and SSM by ARFI are noninvasive diagnostic tools that may help in diagnosing CSPH. LSM and SSM could be used as a guiding noninvasive screening tool in patients with esophageal varices requiring endoscopic evaluation.
Keywords: HVPG; ARFI; portal hypertension; liver stiffness; spleen stiffness